IN VITRO ANTIBACTERIAL PROFILE OF ALSTONIA VENENATA R. BR-A COMPARATIVE STUDY - Thomas, Shirly K.; George, Roshin Elizabeth; Kunjumon, Manesh; Thankamani, V. (International Journal of Current Pharmaceutical Research, 2015)
Objective: To investigate the antibacterial efficacy of leaves, stem-bark, root-bark, flowers and fruits of Alstonia venenata R. Br. Methods: The antimicrobial efficacy of butanol and methanol solvent extracts was evaluated by agar well diffusion against selected pathogenic bacterial strains. Gram negative strains like Pseudomonas aerugenosa, Proteus vulgaris, Escherichia coli, Klebsiella pneumoniae, Slamonella enteric typhimurium, Salmonella typhi, Salmonella paratyphi A, Shigella spp. were tested. Gram positive strains tested were Micrococcus luteus and Staphylococcus aureus. Minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were determined using macro broth dilution method against clinical isolate of Staphylococcus aureus. Streptomycin 0.125 mg/ml was used as positive control and Dimethyl sulfoxideÂ (DMSO) as the solvent control. Results: Butanol and methanol extracts of all the plant parts are highly effective against Gram positive strains and show moderate inhibition against Gram negative strains. Stem-bark and root-bark butanol were the most effective fractions followed by fruit, flower and leaf extracts. The inhibition zones of Micrococcus luteus and Staphylococcus aureus were 24-26 mm and 18-20 mm respectively. The observed zone size was equal to or greater than the positive control used. The MIC value for stem-bark butanol and root-bark butanol were 0.98 mg/ml and the MBC values were 7.8 mg/ml and 3.9 mg/ml respectively. For fruit, flower and leaf butanol the MIC values were 15.6, 31.25 and 125 mg. Conclusion: The extracts were highly active against Gram positive strains than Gram negative strains. The butanol extracts were the most active fraction followed by the methanol extracts. Highest activity was observed for root-bark and stem-bark followed by fruit, flower and leaf extracts.